A study of the dynamical energy flow in uracil. (August 2015) - Bolognesi, P; O'Keeffe, P; Mazza, T; Bozek, J; Coffee, R; Bostedt, C; Schorb, S; Carron, S; Feifel, R; Mucke, M; Guehr, M; Sistrunk, E F; et al.
Synopsis: The time resolved photoionization of C 1s in uracil following excitation of the neutral molecule by 260 nm pulses has been studied at LCLS.